2013
DOI: 10.4049/jimmunol.1202979
|View full text |Cite
|
Sign up to set email alerts
|

Intrarectal Immunization and IgA Antibody-Secreting Cell Homing to the Small Intestine

Abstract: According to the current paradigm, lymphocyte homing to the small intestine requires the expression of two tissue-specific homing receptors, the integrin α4β7 and the CCL25 receptor CCR9. In this study, we investigated the organ distribution and the homing molecule expression of IgA Ab-secreting cells (ASCs) induced by intrarectal immunization with a particulate Ag, in comparison with other mucosal immunization routes. Intrarectal immunization induces gut-homing IgA ASCs that localize not only in the colon but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…For example, immunization by the intra-rectal route can induce a higher number of Ag-specific IgA C PC in the gut than the intra-nasal immunization route. 59 Once in the LP, these PC have access to survival factors that include APRIL and BAFF secreted by DC 60,61 as well as the production of APRIL from the intestinal epithelium itself 62 . Very recently it was shown that similar to what was observed in the BM, gut eosinophils, can secrete cytokines that promote IgA CSR and IgA C PC survival (APRIL, IL-6), thereby supporting an IgA C PC niche in the gut.…”
Section: Plasma Cell-intrinsic Mechanisms Of Survivalmentioning
confidence: 99%
“…For example, immunization by the intra-rectal route can induce a higher number of Ag-specific IgA C PC in the gut than the intra-nasal immunization route. 59 Once in the LP, these PC have access to survival factors that include APRIL and BAFF secreted by DC 60,61 as well as the production of APRIL from the intestinal epithelium itself 62 . Very recently it was shown that similar to what was observed in the BM, gut eosinophils, can secrete cytokines that promote IgA CSR and IgA C PC survival (APRIL, IL-6), thereby supporting an IgA C PC niche in the gut.…”
Section: Plasma Cell-intrinsic Mechanisms Of Survivalmentioning
confidence: 99%
“…(See color plate section.) oxidative conversion of retinoids such as dietary vitamin A (Hammerschmidt et al, 2011), and high expression of α4β7 seems to be most decisive (Agnello et al, 2013). In the large intestine α4β7 appears to be assisted in the homing by the mucosa-associated epithelial chemokine MEC/ CCL28 as an additional cue for attracting circulating IgA + plasmablasts that coexpress high levels of CCR10 , as documented in humans after administration of oral Salmonella vaccinecontrasting the results obtained after parenteral vaccination (Sundström et al, 2008).…”
Section: Adhesion Molecules and Chemokines Of Gut Lamina Propriamentioning
confidence: 87%
“…21 , 30 In contrast, IgA-secreting cells primed at other mucosal inductive sites, such as those elicited by IN immunization in the LNs associated with airways, cannot efficiently occupy plasma cell niches in intestinal sites. 31 In addition, α4β7 +  plasma and memory B cells can be found after infection or experimental challenge with enteric pathogens as well as oral immunization. 32 These differential localization/homing of effector immune cells should be responsible for different immune response patterns in various organs and tissues.…”
Section: Discussionmentioning
confidence: 99%